PENGARUH TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA KARYAWAN DAN KUALITAS PRODUK PADA PT. KIMIA TIRTA UTAMA DI KECAMATAN KOTO GASIB, KABUPATEN SIAK - Erdiani Mariana; Efni Yulia; Paramitha Anggia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effects of Total Quality Management (TQM) on employee performance and product quality. The population in this study includes all the employees at PT. Kimia Tirta Utama. Primary data was collected by questionaire as an instrument to prove the results of the research, to test the hypothesis in this study is using path analysis (path analysis). The sampling technique is a purposive sampling technique (118 employees at PT. Kimia Tirta Utama). The result showed that: (1). Total Quality Management (TQM) to have a significant positive to employee performance, (2).Total Quality Management (TQM) to have a significant positive to product quality, (3).employee performance to have significant positive to product quality, and (4). Total Quality Management (TQM) to have a significant positive to product quality through employee performance.Keywords : Total Quality Management (TQM), Employee Performance, and Quality Product